Optimization of process factor and characterization of vinegar-like beverage production via spontaneous fermentation from pineapple peel waste - Selvanathan, Yashini; Nasratun, Masngut (Elsevier, 2023)
A feasible approach to compensating for pineapple wastage is by utilizing the waste. In the present study, pineapple peels were subjected to spontaneous fermentation to produce a vinegar-like beverage. Based on the central composite design (CCD) approach, optimization of the process factor recorded a maximum total acid yield, Yp/s, and total acidity of 0.49 and 3.03%, respectively. Furthermore, the beverage possessed increased tartaric, citric, ascorbic, acetic, and ferulic acids at a maximum of 1.196%. The cytotoxicity activity toward the human colorectal adenocarcinoma cell line documented a half maximal inhibitory concentration (IC50) at 3.4% v/v of the beverage. This study showcased optimized vinegar-like beverage production by indigenous microorganisms (IMO) with pineapple peel. The beverage contained improved organic and phenolic acids contents and antioxidant potential, which could be employed as a possible human colorectal cancer cure.